Exploring the potential of Halomonas levan and its derivatives as active ingredients in cosmeceutical and skin regenerating formulations - GÖKALSIN, BARIŞ (My University, 2023)
Demand on natural products that contain biological ingredients mimicking growth factors and cytokines made natural polysaccharides popular in pharmaceutical and cosmetic industries. Levan is the β-(2-6) linked, nontoxic, biocompatible, water-soluble, film former fructan polymer that has diverse applications in pharmacy and cosmeceutical industries with its moisturizing, whitening, anti-irritant, anti-aging and slimming activities. Driven by the limited reports on few structurally similar levan polymers, this study presents the first systematic investigation on the effects of structurally different extremophilic Halomonas levan polysaccharides on human skin epidermis cells. In-vitro experiments with microbially produced linear Halomonas levan (HL), its hydrolyzed, (hHL) and sulfonated (ShHL) derivatives as well as enzymatically produced branched levan (EL) revealed increased keratinocyte and fibroblast proliferation (113–118 %), improved skin barrier function through induced expressions of involucrin (2.0 and 6.43 fold changes for HL and EL) and filaggrin (1.74 and 3.89 fold changes for hHL and ShHL) genes and increased type I collagen (2.63 for ShHL) and hyaluronan synthase 3 (1.41 for HL) gene expressions together with fast wound healing ability within 24 h (100 %, HL) on 2D wound models clearly showed that HL and its derivatives have high potential to be used as natural active ingredients in cosmeceutical and skin regenerating formulations.
Keywords: Levan polysaccharide; Chemical modification; Enzymatic production; Skin regeneration; Cosmeceuticals; Wound healing